As queixas escolares e a sua relação com transtornos do neurodesenvolvimento: uma análise crítica à Luz da Teoria Histórico-Cultural - Martini, Emanuelle Luana (2024)
This research is part of the contributions from the Research Group on Teaching, Learning, and Historical-Cultural Theory (GEPEATH) and falls within the research line "Culture, Educational Processes, and Teacher Training," which investigates the relationships between culture and education, teacher training, as well as formal and informal educational processes, encompassing theoretical, practical, socio-political, and pedagogical aspects. Our research is qualitative in nature, specifically a case study, using document analysis as the methodology. The research field was the Municipal Department of Education (SEMED) in the municipality of Coronel Vivida-PR, with the analysis based on documents involving school complaints and diagnostic reports stored in the records of children monitored by the psychology team at SEMED. The general objective of the research was to identify and understand which school complaints resulted in diagnoses of neurodevelopmental disorders. To achieve this, we conducted a critical reflection on the tendency to attribute the lack of learning of school content and behaviors considered unexpected in the school context to exclusively biological causes, disregarding the fundamental role of the social and cultural context in the formation of the individual. We investigated the implications of this diagnostic process for pedagogical practice and children's development. The research sought to highlight which school complaints resulted in neurodevelopmental disorder diagnoses, as well as to discuss broader issues related to the school context, social and cultural interrelations for human development. We used the foundations of Historical-Cultural Theory as a theoretical framework, considering that this perspective is the most enlightening for understanding human development, especially in the way social relationships influence this process. From this perspective, we discussed the role of the school as a space for cultural mediation, in which the development of higher psychological functions occurs dialectically, in constant interrelation with the environment. The analysis aimed to uncover what school complaints are and their historical process, as well as the definition of neurodevelopmental disorders, and finally, the understanding of human development and the learning process. Based on the results obtained, the main school complaints identified in the research were attention difficulties, agitation and restlessness behaviors, and difficulties in learning reading and writing. The conclusion highlighted that the main school complaints that resulted in diagnoses of neurodevelopmental disorders reflect the pressures of the educational system for individual explanations of a biological nature. These complaints, based on a model of the "ideal student" that does not consider the multiple determinations of the individual, but rather presumes expected behaviors for the school context, serve as a reference that guides pedagogical practice. However, the individual does not present themselves at school as someone molded to the system's demands, but rather as the result of multiple determinations that manifest through their behaviors. Finally, we aim to contribute to a critical reflection on school complaints and the diagnoses of neurodevelopmental disorders.